2014
DOI: 10.4236/jct.2014.58089
|View full text |Cite
|
Sign up to set email alerts
|

Side Effects of Chemotherapy in Cancer Patients and Evaluation of Patients Opinion about Starvation Based Differential Chemotherapy

Abstract: Side-effects associated with the cancer chemotherapy limit the scope of chemotherapeutic drugs and no data was available about these side effects in Pakistan. Moreover starvation based differential chemotherapy has been proved to greatly reduce the side effects of chemotherapy depending on starvation time. The current study was conducted to survey the common side effects of the chemotherapeutic drugs and the role of starvation to reduce them. The study included total 100 subjects with multiple carcinomas. A co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
85
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(90 citation statements)
references
References 14 publications
1
85
0
4
Order By: Relevance
“…Although conventional treatments consisting of surgical resection, radiotherapy and chemotherapy are e ective in managing many of the patients (generally prolonged life or permanent cure of cancer), almost 50% of the cases are unmanageable. Also the side e ects such as pain, blood clots, fatigue, anemia, thrombocytopenia, constipation, diarrhea, or neurological complications and unpleasant to fatal infections are very o en accompanied by these treatments (Aslam et al, 2014).…”
mentioning
confidence: 99%
“…Although conventional treatments consisting of surgical resection, radiotherapy and chemotherapy are e ective in managing many of the patients (generally prolonged life or permanent cure of cancer), almost 50% of the cases are unmanageable. Also the side e ects such as pain, blood clots, fatigue, anemia, thrombocytopenia, constipation, diarrhea, or neurological complications and unpleasant to fatal infections are very o en accompanied by these treatments (Aslam et al, 2014).…”
mentioning
confidence: 99%
“…There was also a decrease (statistically non-significant) for mild mouth ulcers, moderate constipation and moderate diarrhea. As the duration of cancer and hence the chemotherapy cycles increases, the occurrence of some adverse drug effects also increases (27). The occurrence of ADRs may be related to patients' characteristics such as age, gender (females), polypharmacy, and co-morbidities.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Huan-Keat Chan and Sabrina Ismail assessed the most common adverse effects occurred by chemotherapy administartion and reported that patients experienced (83.3%) nausea, (78.9%) vomiting, (23.3%) loss of appetite and (6.7%) peripheral neuropathies (31). The findings of a study by Muhammad Shahbaz Aslam showed that after chemotherapy administartion, the majority of patients were suffering from weakness (95%), fatigue (90%) nausea (77%), vomiting (75%) and numbness (49%) (27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current anticancer drugs often have a poor therapeutic index and they cause a lot of side effects [22]. A major concern is when the medications affect non-cancer cells, causing the adverse reduction of red and white blood cells, and affecting the gastrointestinal tract triggering nausea and diarrhea [23]. To reduce, or even better to avoid such side effects, the drug delivery to the tumor is optimized by preparing carriers containing an active agent associated with a molecule capable to accurately target cancer cells such as antibody drug conjugates (ADC) or nanoparticles [24][25][26].…”
Section: Introductionmentioning
confidence: 99%